Foreword from director - Haneef, Sayed Sikandar Shah (Islamic Book Trust, 2020)
There are hosts of issues that Muslim families confront both at the global and local levels due to Tsnimic changes that are happening around us. This piece elucidates the need for having a national forum to discuss family fiqhi issues in Malaysia.